Experiencing teaching history during Work Integrated Learning (WIL) / Teaching Practice during the COVID-19 Pandemic (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
One aspect of history education that was radically impacted on by COVID-19 was the annual WIL/Teaching Practice undertakings by pre-service history teachers. In this, the July 2021 edition, we have tried to capture some of the experiences of pre-service history teachers related to this key aspect of their professional development. This was done by means of a series of short autoethnographic-like pieces in which prospective history teachers of six southern African universities have shared their experiences.